Cerebrovascular accident during competitive karate as a consequence of hypertension? - Baker, J. S; Graham, M.R.; Davies, B. (Journal of Exercise Physiology online, 2007)
Case Study - The purpose of this study was to identify the prevalence of pre-competition elevated blood pressure and associated cardiovascular risk factors in high intensity full-contact sport, in an attempt to elucidate pathological hypertension from anxiety induced high blood pressure, in a group of male karate practitioners. A 53 year old male karate practitioner presented for a full-contact martial arts competition at a national karate competition, England, UK. He competed for approximately one minute and collapsed in the competitive arena, without sustaining any direct injuries to the head. Examination in the competitive arena revealed an individual who was disorientated. He was immediately disqualified from the contest on medical grounds and conveyed to the medical area. On establishing there had been no trauma incurred, the provisional diagnosis was a transient ischemic attack (TIA) from previously undiagnosed hypertension. Cerebral infarction was subsequently diagnosed by magnetic resonance imaging (MRI). MRI represents the only confirmatory sign for the otherwise exclusionary diagnostic procedure for ischemic stroke, but not TIA. Ischemic stroke must be ruled out on follow-up, by MRI, as a key to correct diagnosis. In conclusion, following a head injury in contact sport, an MRI scan is mandatory in diagnosing an intra-cerebral event. The subject gave written informed consent for the reproduction of the data used in this study. ABSTRACT FROM AUTHOR